Assessing the thermal regime of poorly monitored reservoirs with a combined satellite and three-dimensional modeling approach. Issue 3 (3rd July 2021) - Sharaf, Najwa; Lemaire, Bruno J.; Fadel, Ali; Slim, Kamal; Vinçon-Leite, Brigitte
ABSTRACT: The thermal regime of lakes and reservoirs is a major driver of their functioning, yet water temperature measurements are scarce and time-series are frequently interrupted by missing data in many lakes and reservoirs. Our aim was to assess whether satellite imagery combined with 3-dimensional (3D) modeling can overcome this limitation. We assessed the performance of a 3D model (Delft3D-Flow) and compared simulated temperature to satellite data on Karaoun Reservoir in a semiarid region of Lebanon. Surface water temperatures were retrieved from Landsat 8, atmospherically corrected using a single channel algorithm and adjusted with in situ measurements as a proxy of bulk temperatures. With limited calibration, the model reproduced water level fluctuations, water temperature, stratification, and mixing, with low discrepancies from measurements. Satellite temperatures agreed well with observations and simulations. Satellite temperature distribution across the reservoir exhibited low spatial heterogeneity. The 3D model partly reproduced this spatial distribution of surface temperature and generally was able to simulate the thermal regime of the reservoir with limited datasets for initial conditions and for hydrological and meteorological forcing, and with limited calibration. For validating 3D hydrodynamic models, satellite temperatures constitute a valuable source of data complementary to point measurements. Coupling satellite imagery and modeling can improve operational surveys of poorly monitored lakes and reservoirs and enhance knowledge of their thermal functioning.